Balance rehabilitation therapy by tongue electrotactile biofeedback in patients with degenerative cerebellar disease - Cakrt, Ondřej; Vyhnálek, Martin; Slabý, Kryštof; Funda, Tomáš; Vuillerme, Nicolas; Kolář, Pavel; Jeřábek, Jaroslav (NeuroRehabilitation, 2012)
Few clinical studies have evaluated physiotherapeutic interventions in patients with degenerative cerebellar ataxia. Investigations on the effectiveness of biofeedback-based interventions for training postural control in these patients have not been conducted yet. The aim of the present study was to assess the effectiveness of a 2-week intensive tongue-placed electrotactile biofeedback program for patients with progressive cerebellar ataxia. Subjects were seven adult patients suffering from cerebellar degeneration. Postural control was assessed with static posturography in two sensory conditions eyes open/closed on firm surface. For quantification of postural behavior, we used area, sway path and mean velocity of the centre of foot pressure (CoP). Effects of treatment were determined by comparing Pre, Post and one month follow-up (Retention) experimental sessions. Analysis of measured CoP parameters for tests on firm surface showed a significant main effect of visual condition and no difference across test sessions under open eyes condition. Under eyes closed condition, there were significant differences between Pre versus Post and Pre versus Retention, while the difference Post versus Retention was not significant. Our results suggest that a balance rehabilitation program with postural exercise performed with a head position-based tongue-placed biofeedback system could significantly improve bipedal postural control in patients suffering from degenerative cerebellar ataxia.
Keywords: senioři; propriocepce; Biofeedback, Psychology; nemoci mozečku; výsledek terapie; Middle Aged; Postural Balance; mužské pohlaví; Adult; Cerebellar Diseases; Touch; Proprioception; ženské pohlaví; Humans; biofeedback (psychologie); lidé středního věku; Tongue; posturální rovnováha; dospělí; neurodegenerativní nemoci; Female; Aged; Treatment Outcome; Neurodegenerative Diseases; lidé; Male; jazyk; hmat